Penggunaan Qawā’id Fiqhiyyah sebagai Metodologi Istinbat Hukm oleh Majlis Tarjih Muhammadiyah dan Lajnah Bahsul Masail (LBM) Nahdhatul Ulama (NU): The Use Qawā’id Fiqhiyyah as a Legal Istinbath Methodology by the Majlis Tarjih Muhammadiyah and Lajnah Bahsul Masail (LBM) of Nahdhatul Ulama (NU) - Safriadi, Safriadi (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
Qawā'id Fiqhiyyah has an important role and position in the legal discovery process by the Tarjih Council and LBM NU, as stated in the framework of the Majlis Tarjih and LBM NU. This research focuses on answering 2 important things, 1) the use of the Qawā'id Fiqhiyyah mechanism as a methodological argument, 2) the contribution of Qawā'id Fiqhiyyah to contemporary legal discoveries in Lajnah Bahsul Masail (LBM) Nahdhatul Ulama (NU) and Majlis Tarjih Muhammadiyah. This research is an analytical and qualitative descriptive research with a logical philosophical and empirical approach. The results are first. The mechanism for using Qawā'id Fiqhiyyah as methodological proof is carried out by linking (Ilḥāq) a new case with an old case that already has a legal answer under the basis of Qawā’id Fiqhiyyah . Second, the contribution of Qawā'id Fiqhiyyah in the discovery of contemporary law in the LBM as a reinforcement for the decisions taken, is used as supporting evidence, especially since tanẓīr and ilḥāq are needed to develop the insight of Fiqh, but if the main evidence is that no legal answers are found, Meanwhile, Qawā'id Fiqhiyyah contribusion the Muhammadiyah Tarjih Council is the main evidence for finding/istinbāṭ law. From these two institutions it can be analyzed that Qawā'id Fiqhiyyah is used and required in legal istinbāt, but the proportion is still supporting the main evidence.